Antiepileptogenic and Neuroprotective Effects of Pergularia daemia on Pilocarpine Model of Epilepsy - Kandeda, Antoine K.; Taiwe, Germain S.; Moto, Fleur C. O.; Ngoupaye, Gwladys T.; Nkantchoua, Gisele C. N.; Njapdounke, Jacqueline S. K.; Omam, Jean P. O.; Pale, Simon; Kouemou, Nadege; Ngo Bum, Elisabeth (Frontiers in Pharmacology, 2017)
In this study, we investigated antiepileptogenic and neuroprotective effects of the aqueous extract of Pergularia daemia roots (PDR) using in vivo and in vitro experimental models. In in vivo studies, status epilepticus caused by pilocarpine injection triggers epileptogenesis which evolves during about one to two weeks. After two hours of status epilepticus, mice were treated during epileptogenesis period for 7 days with sodium valproate and vitamin C (standards which demonstrated to alter epileptogenesis), or Pergularia daemia. Immediately, animals were challenged with a convulsant. The challenge was represented by acute pentylentetrazole administration one week after status epilepticus. The challenge with PTZ was used to test behaviorally the susceptibility to a convulsant agent with or without treatment with the plant extract. Then, memory was assessed after pentylenetetrazole administration in the elevated plus maze and T-maze paradigms 24 and 48 hours, respectively. Antioxidant and acetylcholinesterase activities were determined in the hippocampus after sacrifice, whereas in vitro studies were conducted using embryonic rat primary cortical cultures exposed to L-glutamate. Cell survival rate was measured and apoptotic and necrotic cell death determined. Chronic oral administration of PDR significantly and dose-dependently increased the latency to myoclonic jerks, clonic seizures and generalized tonic-clonic seizures, and the seizure score. In addition, PDR at all doses (from 4.9 to 49 mg/kg) significantly decreased the initial and retention transfer latencies in the elevated plus maze. Interestingly PDR at the same doses significantly increased the time spent and the number of entries in T-maze novel arm. PDR significantly increased the activities of acetylcholinesterase and antioxidant enzymes superoxide dismutase, catalase, and total glutathione and proteins, and decreased malondialdehyde level. Furthermore, PDR increased viability rate of primary cortical neurons after L-glutamate-induced excitotoxicity, in dose dependent manner. These results suggest that PDR has antiepileptogenic and neuroprotective effects, which could be mediated by antioxidant and anti-apoptotic activities.